Aspergillus coinfection in critically Ill patients with severe dengue - Yang-Han Lin; Ting-Chia Chang; Wen-Liang Yu; Willy Chou; Chin-Ming Chen (Journal of Infection and Public Health, 2023)
In 2014–2015, a significant outbreak of dengue fever occurred in southern Taiwan, with a subsequent decline in dengue incidence. Despite this, there is emerging concern about virus-associated aspergillosis, yet limited research has explored coinfections involving dengue and aspergillosis. We conducted a retrospective study at a single center in Southern Taiwan, specifically focusing on dengue patients admitted to the intensive care unit during the period between July and November 2015. Among the 142 dengue patients studied, only 8.06 % (10/142) underwent serum galactomannan testing, with a single patient undergoing bronchoalveolar lavage (BAL) galactomannan assay. Out of those tested, 20 % (2/10) returned positive serum galactomannan results. Herein, we present two consecutive cases of coinfection involving dengue and pulmonary aspergillosis in immunocompetent patients.